2020
DOI: 10.1101/2020.01.30.914747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distinct neural ensemble response statistics are associated with recognition and discrimination of natural sound textures

Abstract: The perception of sound textures, a class of natural sounds defined by statistical sound structure such as fire wind, and rain, has been proposed to arise through the integration of time-averaged summary statistics. Where and how the auditory system might encode these summary statistics to create internal representations of these stationary sounds, however, is unknown. Here, using natural textures and synthetic variants with reduced statistics, we show that summary statistics modulate the correlations between … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Sensory systems differentially encode environmental stimuli depending on the context in which they are encountered (De Franceschi & Barkat, 2020;Herrmann et al, 2015;Jaramillo et al, 2014;Pakan et al, 2016;Takesian et al, 2018;Zhai et al, 2020). The same physical stimulus can elicit distinct neuronal responses depending on whether it is predictable or unexpected in a given sensory stream (Weissbart et al, 2020;Yaron et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Sensory systems differentially encode environmental stimuli depending on the context in which they are encountered (De Franceschi & Barkat, 2020;Herrmann et al, 2015;Jaramillo et al, 2014;Pakan et al, 2016;Takesian et al, 2018;Zhai et al, 2020). The same physical stimulus can elicit distinct neuronal responses depending on whether it is predictable or unexpected in a given sensory stream (Weissbart et al, 2020;Yaron et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are no theories for how such cue interactions come about. One well-supported theory is that perception is strongly influenced by statistical variations of acoustical cues found in natural sounds (Elliott and Theunissen, 2009;Geffen et al, 2011;McDermott and Simoncelli, 2011;Zhai et al, 2020) Along these lines, we propose that statistical co-variations between onset and duration in natural sounds could explain why sound onsets strongly influence the perception of sound duration.…”
Section: Introductionmentioning
confidence: 65%
“…Thus, since local features are not retained after averaging (McDermott, Schemitsch, and Simoncelli, 2013), it is possible to conclude that the two computations represent alternative processes, and the system switches from one to the other depending on the intrinsic sound properties (e.g., statistical variability) and the amount of available information in the auditory stream (e.g., increased stimulation length). Recent evidence in the animal model showed that auditory statistics ensembles are represented by distinct responses at the level of the midbrain (Zhai et al, 2020). These neural representations to auditory statistics occur at dissociable time scales, permitting the discrimination and recognition of natural sounds, with local information supporting sounds differentiation while the emergence of global structure their recognition (Zhai et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence in the animal model showed that auditory statistics ensembles are represented by distinct responses at the level of the midbrain (Zhai et al, 2020). These neural representations to auditory statistics occur at dissociable time scales, permitting the discrimination and recognition of natural sounds, with local information supporting sounds differentiation while the emergence of global structure their recognition (Zhai et al, 2020). In our study, whole brain results in the source domain (Figure 3 Conversely, the same contrast at long durations linked the emergence of global discrimination predominantly to the left hemisphere: precisely, response peaked both around Heschl's gyrus, corresponding to early auditory cortex, and in the STS and STG; Figure 3A).…”
Section: Local and Global Discrimination Subtend To Alternative Proce...mentioning
confidence: 99%